Carboxymethyl cellulose hydrogel from biomass waste of oil palm empty fruit bunch using calcium chloride as crosslinking agent - Tuan Mohamood, Nur Fattima’ Al-Zahara’; Abdul Halim, Abdul Hakam; Zainuddin, Norhazlin (Multidisciplinary Digital Publishing Institute, 2021)
Carboxymethyl cellulose (CMC) is modified cellulose extracted from oil palm empty fruit bunch (OPEFB) biomass waste that has been prepared through etherification using sodium monochloroacetate (SMCA) in the presence of sodium hydroxide. In this research, CMC hydrogel was prepared using calcium chloride (CaCl2) as the chemical crosslinker. Throughout the optimization process, four important parameters were studied, which were: (1) CMC concentration, (2) CaCl2 concentration, (3) reaction time, and (4) reaction temperature. From the results, the best gel content obtained was 28.11% at 20% (w/v) of CMC with 1% (w/v) of CaCl2 in 24 h reaction at room temperature. Meanwhile, the degree of swelling for CMC hydrogel was 47.34 g/g. All samples were characterized using FT-IR, XRD, TGA, and FESEM to study and compare modification on the OPEFB cellulose. The FT-IR spectrum of CMC hydrogel showed a shift of COO− peaks at 1585 cm−1 and 1413 cm−1, indicating the substitution of Ca2+ into the CMC molecular chains. The XRD diffractogram of CMC hydrogel showed no observation of sharp peaks, which signified an amorphous hydrogel phase. The CrI value also proved the decrement of the crystalline nature of CMC hydrogel. TGA–DTG thermograms showed that the Tmax of CMC hydrogel at 293.33 °C is slightly better in thermal stability compared to CMC. Meanwhile, the FESEM micrograph of CMC hydrogel showed interconnected pores indicating the crosslinkages in CMC hydrogel. CMC hydrogel was successfully synthesized using CaCl2 as a crosslinking agent, and its swelling ability can be used in various applications such as drug delivery systems, industrial effluent, food additives, heavy metal removal, and many more.